Preparation method of low-aluminum titanium-doped iron phosphate
Patent Information
- Application Number
- CN202611388165.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-20
AI Technical Summary
[0006]针对现有技术的不足,本发明提供了一种低铝掺钛磷酸铁的制备方法,该工艺能够解决现有技术中需要额外除铝增加工艺成本、铝杂质进入产品晶格导致产品纯度下降等问题
1.实现了铝杂质的原位化学抑制,从源头解决铝共沉淀问题
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of ferric phosphate preparation technology, specifically a method for preparing low-aluminum titanium-doped ferric phosphate. Background Technology
[0002] Lithium iron phosphate (LFP) has become one of the most important cathode materials in the fields of power batteries and energy storage due to its high safety, long cycle life, and low cost. However, its intrinsically low ionic and electronic conductivity limits its high-rate performance. Elemental doping is an effective means to improve the electrochemical performance of LFP, among which titanium doping has attracted much attention due to its ionic radius compatibility and oxidation state stability.
[0003] Ferric phosphate, as the main precursor in the synthesis of lithium iron phosphate, directly affects the performance of the final cathode material. In existing technologies, the co-precipitation method is commonly used to prepare titanium-doped ferric phosphate. This involves using ferrous salts, phosphorus sources, titanium sources, and oxidants as raw materials, generating the titanium-doped ferric phosphate precursor through a co-precipitation reaction, followed by aging, drying, and calcination to obtain the final product. In the co-precipitation method for preparing titanium-doped ferric phosphate, the purity of the raw materials has a decisive impact on product quality. The titanium source is the main raw material for introducing titanium, but industrial-grade titanium sources such as titanium oxysulfate, titanium tetrachloride, and metatitanic acid inevitably contain a certain amount of aluminum impurities during production or storage. Taking titanium oxysulfate as an example, its raw material, titanium concentrate, often contains associated aluminum oxides. During the sulfuric acid process for preparing titanium oxysulfate, aluminum will be converted into Al... 3+ These aluminum impurities are introduced into the titanium source product. Once introduced into the reaction system along with the titanium source, they cause serious co-precipitation pollution during the co-precipitation reaction. Specifically, according to the solubility product theory, the solubility product of hydrated iron phosphate is similar to that of aluminum phosphate, while the solubility product of aluminum hydroxide is lower. During the co-precipitation reaction, with the consumption of iron ions and the increase of the reaction pH, the Al in the system... 3+ It readily combines with phosphate and / or hydroxide ions to form aluminum phosphate or aluminum hydroxide precipitates, which precipitate together with the target product, titanium-doped iron phosphate, resulting in aluminum impurities entering the product lattice. The presence of even a small amount of aluminum impurities can adversely affect the electrochemical performance of lithium iron phosphate, such as reducing specific capacity and deteriorating cycle stability.
[0004] To address the problems caused by aluminum impurities in titanium sources, existing technologies mainly employ the following treatment strategies: First, pretreatment of the titanium source before co-precipitation reaction to remove impurities. This involves pre-treating the titanium source to remove aluminum before introducing it into the reaction system. For example, the pH of the titanium-containing solution can be adjusted by hydrolysis to hydrolyze aluminum ions into aluminum hydroxide precipitate, which is then removed by filtration; or solvent extraction or ion exchange methods can be used to selectively separate aluminum impurities. For instance, patent CN121931344A discloses a titanium-containing iron phosphate and its preparation method, which involves introducing acid into an aluminum-removing filter press for acid washing, and then mixing the washing solution with the titanium source; patent CN118026125B discloses a method for recovering battery-grade iron phosphate from waste lithium iron phosphate battery black powder, which involves removing copper, aluminum, and titanium from the acid leaching solution. While these methods can control the entry of aluminum impurities into the reaction system at the source, they increase the investment in independent pretreatment processes and equipment, prolong the process flow, significantly increase production costs, and may cause loss of titanium elements during the impurity removal process. Secondly, precipitation separation and impurity removal during the coprecipitation reaction process. This involves adjusting the pH of the reaction system or adding a precipitant during the coprecipitation reaction to cause aluminum ions to precipitate as aluminum phosphate or aluminum hydroxide, which is then separated from the target product through filtration or other methods. For example, patent CN113816353B discloses a method for removing aluminum from the acid leaching solution of waste lithium iron phosphate batteries through iron-aluminum coprecipitation. This method controls the pH and temperature conditions of the leaching solution to conduct the coprecipitation reaction, obtaining an aluminum-iron coprecipitate and a solution after aluminum removal. Patent CN117585653B discloses a method for preparing low-cost battery-grade iron phosphate through multiple precipitation processes, separating impurities such as aluminum from the product through precipitation, dissolution, and reprecipitation. However, because the precipitation conditions of aluminum phosphate, aluminum hydroxide, and iron phosphate, such as pH range and temperature, highly overlap, selective precipitation separation is difficult to achieve in practice, and some aluminum impurities inevitably enter the product. Thirdly, impurity removal during the aging stage after the coprecipitation reaction. In the aging and crystallization stage after the co-precipitation reaction, specific additives are added to remove aluminum impurities that have entered the precipitate from the crystal lattice through competitive crystallization or adsorption-displacement. For example, patent CN122079104A discloses a high-purity homogeneous titanium-doped iron phosphate and its low-cost preparation method. Specific additives such as ferrous phosphate, pure ferrous sulfate heptahydrate, and ferrous dihydrogen phosphate are added during the aging and crystallization stage. Through competitive crystallization or adsorption-displacement, aluminum, magnesium, and other impurity ions are removed from the crystal lattice or adsorbed onto the crystal surface for subsequent washing. Patent CN1190547A discloses a low-impurity iron phosphate, its preparation method, and its application. The first slurry is heated and aged, utilizing the difference in solubility products between iron phosphate and aluminum phosphate to cause aluminum to deposit first, thus achieving the removal purpose. However, this method can only remove some aluminum impurities adsorbed on the surface or encapsulated in crystal lattice defects; its removal effect on aluminum dopants that have already entered the crystal lattice is very limited.Furthermore, in the field of waste lithium iron phosphate material recycling, research has proposed aluminum removal technologies based on fluoride ion-mediated processes. For example, patent CN112310500A discloses a method for separating aluminum from waste lithium iron phosphate materials, which involves adding a fluoride-containing complexing agent to an acid leaching solution containing aluminum, and using the complexation reaction principle to achieve aluminum precipitation and separation under acidic conditions. Patent CN117466265B discloses a method for removing fluoride-aluminum from the positive and negative electrode powders of waste lithium iron phosphate batteries, which involves adding aluminum and fluoride precipitants to an acid leaching solution for precipitation reaction, resulting in a defluorinated and aluminum-removed purified solution. However, these technologies are mainly applied to aluminum removal in waste battery recycling scenarios, and have not yet been applied to the synthesis process of virgin titanium-doped lithium iron phosphate, and their essence still belongs to the precipitation separation approach.
[0005] Therefore, there is an urgent need to develop a method for preparing titanium-doped iron phosphate that does not require pre-aluminum removal from the titanium source, effectively suppresses aluminum impurities introduced from the titanium source from entering the product lattice, and achieves in-situ chemical regulation of aluminum during the synthesis process. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this invention provides a method for preparing low-aluminum titanium-doped iron phosphate. This process can solve problems such as the need for additional aluminum removal, which increases process costs, and the decrease in product purity caused by aluminum impurities entering the product lattice.
[0007] To address the above technical problems, this invention provides a method for preparing low-aluminum titanium-doped iron phosphate, comprising the following steps: S1. Raw material system construction: Weigh out ferrous source, phosphorus source, oxidant, aluminum-containing titanium source, and ligand that can coordinate with aluminum ions as raw materials for later use; S2, Co-precipitation reaction: The raw materials are mixed, and then a precipitant is added to adjust the pH to carry out a co-precipitation reaction to obtain titanium-doped iron phosphate slurry; S3. Post-processing: The titanium-doped iron phosphate slurry is subjected to a first solid-liquid separation to obtain a first filter residue and a first filtrate. The first filter residue is washed, and the washed filter residue is slurried with water and the solid content is adjusted before adding phosphoric acid for aging to obtain an aged slurry. The aged slurry is subjected to a second solid-liquid separation, and the obtained solid is washed, dried, and calcined to obtain a low-alumina titanium-doped iron phosphate product.
[0008] Furthermore, in S1, the ferrous source includes one or more of ferrous sulfate, ferrous chloride, ferrous nitrate, and ferrous phosphate; the phosphorus source includes one or more of phosphoric acid, monoammonium phosphate, diammonium dihydrogen phosphate, and diammonium phosphate; the aluminum-containing titanium source includes one or more of titanium oxysulfate, titanium oxychloride, and titanium sulfate prepared from industrial-grade titanium ore; and the oxidant is one or more of hydrogen peroxide, air, oxygen, and ozone.
[0009] Furthermore, in S1, the molar ratio of iron to phosphorus in the ferrous source and phosphorus source is 0.95~1.05; the amount of oxidant used is such that the Fe in the ferrous source... 2+ Completely oxidized to Fe 3+ The required theoretical molar amount is 110% to 130%.
[0010] Furthermore, in S1, the ligand is a fluorine-containing ligand; the molar ratio of the ligand to the aluminum element in the aluminum-containing titanium source is 1~100:1.
[0011] Furthermore, the fluorine-containing ligand is one or more of ammonium fluoride, sodium fluoride, and potassium fluoride.
[0012] Furthermore, in S2, the precipitant includes one or more of ammonia, sodium hydroxide, and potassium hydroxide; and the pH is adjusted to 1.8-2.2.
[0013] Furthermore, in S2, the ligand is added to at least one of the ferrous source, phosphorus source, aluminum-titanium source, or oxidant before the co-precipitation reaction begins, or is added to the reaction system in parallel with at least one of the ferrous source, phosphorus source, aluminum-titanium source, and oxidant.
[0014] Furthermore, in step S3, the filtrate from the first solid-liquid separation and the wash water after washing the first filter residue are collected. A regenerant is added to the combined liquid of the filtrate and wash water. After solid-liquid separation, the aluminum-containing precipitate is removed to obtain a regenerated mother liquor. After adding a complexing agent to the regenerated mother liquor, the process is returned to step S2 for recycling.
[0015] Furthermore, the regenerant includes one or more of sodium salts, calcium salts, and magnesium salts.
[0016] On the other hand, the present invention provides a low-aluminum titanium-doped iron phosphate prepared by the method described in the first aspect, wherein the aluminum content in the low-aluminum titanium-doped iron phosphate is less than 80 ppm, the titanium content is 500 to 10000 ppm, and the iron-phosphorus molar ratio is 0.95 to 0.97.
[0017] Compared with existing technologies, this solution has the following advantages: 1. It achieves in-situ chemical inhibition of aluminum impurities, solving the problem of aluminum co-precipitation at its source. This invention introduces fluorine-containing ligands such as ammonium fluoride, sodium fluoride, and potassium fluoride into the coprecipitation reaction system. Utilizing the strong coordination between fluoride ions and aluminum ions, a stable, soluble fluorine-aluminum complex is formed. This complex exists stably in solution and does not coprecipitate with phosphate or hydroxide ions. Therefore, in-situ chemical inhibition of aluminum impurities is achieved simultaneously with the coprecipitation reaction, rather than traditional physical separation. This mechanism prevents aluminum impurities from entering the product crystal lattice at the source, solving the technical problem of selective separation due to similar solubility products in existing technologies. In contrast, if the ligand is added after the coprecipitation reaction (as shown in Comparative Example 2), the aluminum ions that have entered the ferric phosphate precipitate cannot be "pulled back" into the solution, and the aluminum content in the product remains as high as 146 ppm, comparable to Comparative Example 1 (156 ppm) without the ligand. This indicates that the ligand must be added during the coprecipitation reaction (before or during) to effectively inhibit aluminum coprecipitation in situ.
[0018] 2. It enables the recycling and regeneration of the complexing agent and the reuse of the mother liquor, significantly reducing costs and environmental impact. This invention collects the mother liquor containing fluorine-aluminum complexes after the coprecipitation reaction. By adding a regenerator, aluminum ions in the mother liquor selectively precipitate with some of the complexing agent. After solid-liquid separation, the aluminum-containing precipitate is removed. The regenerated mother liquor retains most of the complexing agent with coordination-regulating capabilities. After adding an appropriate amount of fresh complexing agent, it is returned to the coprecipitation reaction for recycling. This closed-loop process realizes the recycling and reuse of complexing agents, significantly reducing the consumption of complexing agents such as fluorides, and reducing the discharge of fluorine-containing wastewater, which meets the requirements of green manufacturing and circular economy development.
[0019] 3. The process is simple, requiring no separate impurity removal step, resulting in significant cost advantages. In existing technologies, regardless of whether pretreatment for impurity removal before reaction, precipitation separation for impurity removal during reaction, or impurity removal during aging, additional operating steps or additives are required. This invention embeds the "coordination inhibition" function into the coprecipitation reaction process, eliminating the need for separate pretreatment of the titanium source for impurity removal, and also eliminating the need for additional impurity removal agents during aging, resulting in a simplified process flow. The coordinating agent can be added to any raw material before the start of the coprecipitation reaction, or it can be added concurrently with the raw materials, offering flexible operation. Furthermore, this invention directly uses aluminum-containing titanium sources such as titanium oxysulfate prepared from industrial-grade titanium ore, eliminating the need for pre-purification of the titanium source and further reducing raw material costs.
[0020] 4. The product has high purity, uniform titanium doping, and excellent electrochemical performance. This invention effectively suppresses aluminum impurities from entering the iron phosphate lattice through the in-situ coordination of a ligand. The resulting low-aluminum titanium-doped iron phosphate product can have an aluminum content below 80 ppm, while the titanium content is flexibly adjustable within the range of 500–10000 ppm. Because the ligand is uniformly distributed throughout the reaction system during the co-precipitation reaction, aluminum ions are effectively "locked" in the solution without interfering with the crystallization process of iron phosphate, ensuring uniform doping of titanium in the iron phosphate lattice. High-purity, uniformly doped titanium-doped iron phosphate, used as a precursor in the preparation of lithium iron phosphate cathode materials, effectively avoids lattice defects and side reactions caused by aluminum impurities, thus improving the material's specific capacity, cycle stability, and rate performance.
[0021] 5. Flexible addition method of the complexing agent, with a wide range of applications. The ligand of the present invention can be added to at least one of a ferrous source, a phosphorus source, an aluminum-titanium source, or an oxidant before the start of the coprecipitation reaction, or it can be added to the reaction system in parallel with at least one of the above raw materials. This flexible addition method allows the present invention to be adapted to different production processes and equipment conditions, and it has good industrial applicability.
[0022] 6. Fluorine-containing complexing agents can be completely removed through post-treatment, eliminating the risk of fluorine residue in the product. This invention achieves in-situ coordination inhibition of aluminum impurities by introducing a fluorine-containing ligand during the co-precipitation reaction stage. Simultaneously, it utilizes the stable existence of fluorine-aluminum complexes in the liquid phase to thoroughly remove them through post-treatment processes such as solid-liquid separation, multiple washing, aging, and high-temperature calcination. Even when the F / Al molar ratio is as high as 80, the fluorine content of the product remains below the detection limit or even undetectable, proving that the ligand has been completely separated from the mother liquor. Therefore, this invention achieves efficient aluminum removal without the risk of fluorine residue, ensuring product purity and its safety in application as a lithium iron phosphate cathode material. Attached Figure Description
[0023] Figure 1 This is a process flow diagram of the present invention; Figure 2 A comparison chart of the Al content in the titanium-doped iron phosphate products prepared in Examples 1-4; Figure 3 This is a comparison chart of the Al content in the titanium-doped iron phosphate products prepared in Example 5 and Comparative Example 1. Detailed Implementation
[0024] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0025] Example 1 This embodiment provides a method for preparing low-aluminum titanium-doped iron phosphate, such as... Figure 1 As shown, it includes the following steps: (1) Raw material preparation Take 500 mL of ferrous sulfate solution with a ferrous concentration of 55.15 g / L, and take 246 mL of ammonium dihydrogen phosphate solution with a phosphorus concentration of 62.19 g / L. Adjust the iron-phosphorus ratio to 1.
[0026] Based on the iron content, the amount of 27.5% hydrogen peroxide required for oxidation is 36.63g. (Based on Fe...) 2+ Completely oxidized to Fe 3+ Based on 120% of the required theoretical molar amount.
[0027] Based on the amount of ferric phosphate that can be prepared, the mass of titanium oxysulfate solution with a titanium content of 7% required to produce 5000ppm titanium-doped ferric phosphate is calculated to be 5.32g.
[0028] (2) Addition of regulators Based on the mass of the titanium oxysulfate solution and the aluminum content, the amount of ammonium fluoride as the complexing agent is calculated to be 0.54 g, and the fluorine-aluminum ratio is 20. The complexing agent is added to the ferrous solution and mixed evenly.
[0029] (3) Coprecipitation reaction Using ferrous sulfate solution as the base solution, and controlling the reaction temperature at 40~50℃, ammonium dihydrogen phosphate, hydrogen peroxide, and titanium oxysulfate solution were added dropwise to the ferrous sulfate solution in a parallel flow. At the same time, 10.4% ammonia solution was used to adjust the pH of the system online to maintain it at 2.0±0.2. After the addition was completed, the temperature was kept high for 1 hour to allow the iron and phosphorus to precipitate completely.
[0030] (4) Product preparation After solid-liquid separation of the slurry obtained from the co-precipitation reaction, the filter residue was washed once with 4 times its weight of water. The solid content was then adjusted to 14%, and the slurry was aged at 95°C with 10% phosphoric acid until it turned completely white, then kept at that temperature for 1 hour. After solid-liquid separation, the filter residue was washed twice with 4 times its weight of water. After drying at 120°C, it was crushed and calcined at 620°C for 3 hours.
[0031] The prepared titanium-doped iron phosphate was tested, and the results are shown in Table 1.
[0032] Example 2 The difference between this embodiment and Example 1 is that the addition of ammonium fluoride as a coordinating agent to the ferrous solution is replaced by the addition of an aluminum-containing titanium source. The composition, dosage, and experimental parameters of the other raw materials are exactly the same as those in Example 1.
[0033] The prepared titanium-doped iron phosphate was tested, and the results are shown in Table 1.
[0034] Example 3 The difference between this embodiment and Example 1 is that the addition of ammonium fluoride as a ligand to the ferrous solution is replaced by the addition of a phosphorus source. The composition, dosage, and experimental parameters of the other raw materials are exactly the same as those in Example 1.
[0035] The prepared titanium-doped iron phosphate was tested, and the results are shown in Table 1.
[0036] Example 4 The difference between this embodiment and Example 1 is that the addition of ammonium fluoride as a coordinating agent to the ferrous solution is replaced with the addition of hydrogen peroxide. The composition, dosage, and experimental parameters of the other raw materials are exactly the same as those in Example 1.
[0037] The prepared titanium-doped iron phosphate was tested, and the results are shown in Table 1.
[0038] Example 5 The difference between this embodiment and Example 1 is that, except for the amount of ligand added, all other experimental conditions are the same as in Example 1.
[0039] In this embodiment, the amount of ammonium fluoride added was adjusted according to the aluminum content in titanium oxysulfate, so that the F / Al molar ratio was 4, 6, 10, 20, 40, 60 and 80 respectively. The same process as in Example 1 was used for in-situ coordination, co-precipitation, aging and product preparation. The aluminum content, titanium content and product phase in the obtained titanium-doped iron phosphate product were detected to determine the optimal ratio of the regulator.
[0040] The prepared titanium-doped iron phosphate was tested, and the results are shown in Table 1.
[0041] Example 6 The difference between this embodiment and Embodiment 1 is that the filtrate from the first solid-liquid separation after the coprecipitation reaction in Embodiment 1 and the wash water after washing the filter residue are collected and combined as the mother liquor.
[0042] Analysis revealed that the mother liquor contained a certain concentration of aluminum ions and unreacted fluorides. Na₂SO₄ solution was added to the mother liquor as a regenerator, maintaining a Na / Al molar ratio of 2.5:1. The mixture was stirred at 25–40°C for 30 min, and the pH was adjusted to 2.2 ± 0.1 using ammonia. The reaction was continued for 1 h. During the reaction, aluminum ions in the mother liquor reacted with some fluoride ions to form an aluminum-containing precipitate. After solid-liquid separation, the precipitate was removed, yielding the regenerated mother liquor.
[0043] The regenerated mother liquor was tested, and it was found that fluorides still remained, which could be used for in-situ coordination regulation. The residual ammonium fluoride equivalent in the regenerated mother liquor was calculated to be 0.26 g. Subsequently, 0.28 g of ammonium fluoride was added to restore the total amount of regulator to the level of Example 1. The ferrous sulfate solution was then reconstituted using this regenerated mother liquor, and titanium-doped ferric phosphate was prepared according to the method described in Example 1.
[0044] The test results are shown in Table 1. The Al content in the obtained titanium-doped iron phosphate product is 17 ppm, and the Ti content is basically the same as that in Example 1. The XRD diffraction peaks of the product are not significantly different from those in Example 1, indicating that the regulator still has good in-situ coordination regulation ability after regeneration and does not affect the titanium doping and the formation of iron phosphate crystal structure.
[0045] To further verify the recycling effect of the regulator, the above-mentioned regenerated mother liquor was continuously recycled three times, with only a portion of the consumed ammonium fluoride replenished each time. The test results showed that the Al content in the products obtained from the first, second, and third cycles was 17 ppm, 13 ppm, and 16 ppm, respectively, all significantly lower than that of Comparative Example 1. Furthermore, the Ti content and phase composition of the products remained stable, indicating that the "in-situ coordination regulation-mother liquor regeneration-recycling" process constructed in this invention has good stability and reusability, effectively reducing regulator consumption and wastewater discharge.
[0046] Comparative Example 1: No ligand added The difference between this comparative example and Example 1 is that ammonium fluoride, the coordinating agent, is not added, while the composition and amount of the remaining raw materials are the same as in Example 1.
[0047] The prepared titanium-doped iron phosphate was tested, and the results are shown in Table 1.
[0048] Comparative Example 2: Adding a complexing agent after co-precipitation. The difference between this comparative example and Example 1 is that the steps for adding ammonium fluoride are different, while the other experimental conditions are the same as in Example 1.
[0049] In this comparative example, the coprecipitation reaction was first completed according to the method of Example 1. After the coprecipitation reaction was completed, 0.54g of ammonium fluoride was added and stirred for 30min. Then, the product was aged, filtered, washed, dried and calcined according to Example 1 to prepare titanium-doped iron phosphate.
[0050] The prepared titanium-doped iron phosphate was tested, and the results are shown in Table 1.
[0051] Table 1 Comparison of key indicators of different embodiments and comparative examples.
[0052] Results analysis: 1. As shown in Table 1 and Figure 2As shown in Examples 1-4, regardless of whether the ligand was added from a ferrous source, phosphorus source, titanium source, or oxidant, the Fe / P molar ratio of the resulting products remained stable between 0.95 and 0.97, and the Ti content remained at approximately 5000 ppm. This indicates that the location of the ligand addition does not affect the composition of the titanium-doped iron phosphate or the titanium doping effect. Simultaneously, the Al content in the products was below 15 ppm, indicating that the ligand could effectively coordinate with Al ions in situ during co-precipitation, significantly inhibiting aluminum impurities from entering the iron phosphate crystals. Furthermore, fluorine was not detected in the titanium-doped iron phosphate products obtained in Examples 1-6, indicating that the fluorine content was below the detection limit of ion chromatography. This is because the soluble complex formed by fluoride ions and aluminum ions is stably present in the liquid phase and is effectively separated with the mother liquor and wash water during the solid-liquid separation and washing process after co-precipitation. The filter residue was further treated with a phosphoric acid system during the aging stage, and subsequent solid-liquid separation and thorough washing further removed any potentially residual trace amounts of fluoride ions. Therefore, the fluorinated ligand used in this invention, after in-situ coordination regulation, can be completely removed through conventional solid-liquid separation and washing processes, without adversely affecting the purity of the final product or the preparation and performance of downstream lithium iron phosphate. In contrast, the Al content of Comparative Example 1 (without ligand) was as high as 156 ppm, indicating that the addition of the fluorinated ligand is a key factor in effectively inhibiting aluminum co-precipitation. The absence of detected fluorine residue in the product further demonstrates that this process effectively removes aluminum while avoiding the residue problem of the ligand itself.
[0053] 2. In Comparative Example 2, a ligand was added after co-precipitation. The resulting titanium-doped iron phosphate product had an Al content of 146 ppm, which was 10 times that of Examples 1-4. This is because aluminum ions had already participated in the co-precipitation and entered the product, and the ligand could no longer exert an in-situ coordination regulation effect on the precipitated aluminum. Therefore, the aluminum content in the product was not significantly reduced. This further proves that the ligand should be added before or during the co-precipitation reaction, rather than after the co-precipitation is completed.
[0054] 3. Example 6 shows that after mother liquor regeneration and regulator reuse, the Al content in the products obtained after three consecutive cycles was 17, 13 and 16 ppm, respectively, all remaining below 20 ppm. The Fe / P molar ratio and Ti content were basically consistent with the first experiment, indicating that the ligand still has good in-situ coordination regulation ability after regeneration, and can be recycled without significantly affecting the composition and doping effect of titanium-doped iron phosphate products.
[0055] 4. In Comparative Example 1, no ligand was added, and the Al content of the product was as high as 156 ppm. In Comparative Example 2, a regulator was added after co-precipitation, and the Al content of the product was still 146 ppm, which was not significantly improved compared with Comparative Example 1. This indicates that the regulator must be involved in the system before or during the co-precipitation reaction in order to inhibit the entry of Al ions into the product through in-situ coordination. However, adding it later can no longer play a regulatory role on the Al that has already been co-precipitated.
[0056] 5. The comparative results of the Al content in the titanium-doped iron phosphate products prepared in Examples 1-4 show that when the ligand is added to the ferrous source, phosphorus source, titanium source or oxidant before the start of the coprecipitation reaction, the Al content in the obtained titanium-doped iron phosphate products is all less than 15 ppm. This indicates that the regulator does not need to be limited to a specific raw material. As long as it can play a coordinating role before the hydrolysis and coprecipitation of aluminum ions in the coprecipitation process, it can effectively inhibit aluminum impurities from entering the product.
[0057] 6. For example Figure 3 As shown, the comparison of Al content in the titanium-doped iron phosphate products prepared in Example 5 and Comparative Example 1 reveals that when the F / Al ratio is below 10, the Al content in the product is 60-100 ppm, which is lower than that in Comparative Example 1 (156 ppm), but still significantly higher than the F / Al range of 10-60 (8-18 ppm). This indicates that insufficient fluoride ion concentration cannot adequately coordinate with aluminum ions. When the F / Al ratio reaches above 10, the Al content drops below 20 ppm and tends to stabilize. When the F / Al ratio exceeds 60, excess fluoride increases the fluoride ion concentration in the system, which is detrimental to production cost control and engineering applications. Considering both the aluminum removal effect and raw material cost, an F / Al ratio of 10-60 is preferred.
[0058] The above descriptions are merely embodiments of the present invention, and common knowledge regarding specific structures and characteristics is not elaborated upon here. It should be noted that those skilled in the art can make various modifications and improvements without departing from the structure of the present invention, and these should also be considered within the scope of protection of the present invention. These modifications and improvements will not affect the effectiveness of the present invention or the practicality of the patent. The scope of protection claimed in this application should be determined by the content of its claims, and the specific embodiments described in the specification can be used to interpret the content of the claims.
Claims
1. A method for preparing low-aluminum titanium-doped iron phosphate, characterized in that: Includes the following steps: S1. Raw material system construction: Weigh out ferrous source, phosphorus source, oxidant, aluminum-containing titanium source, and ligand that can coordinate with aluminum ions as raw materials for later use; S2, Co-precipitation reaction: The raw materials are mixed, and then a precipitant is added to adjust the pH to carry out a co-precipitation reaction to obtain titanium-doped iron phosphate slurry; S3. Post-processing: The titanium-doped iron phosphate slurry is subjected to a first solid-liquid separation to obtain a first filter residue and a first filtrate. The first filter residue is washed, and the washed filter residue is slurried with water and the solid content is adjusted before adding phosphoric acid for aging to obtain an aged slurry. The aged slurry is subjected to a second solid-liquid separation, and the obtained solid is washed, dried, and calcined to obtain a low-alumina titanium-doped iron phosphate product.
2. The method for preparing low-aluminum titanium-doped iron phosphate according to claim 1, characterized in that: In S1, the ferrous source includes one or more of ferrous sulfate, ferrous chloride, ferrous nitrate, and ferrous phosphate; the phosphorus source includes one or more of phosphoric acid, monoammonium phosphate, diammonium dihydrogen phosphate, and diammonium phosphate; the aluminum-containing titanium source includes one or more of titanium oxysulfate, titanium oxychloride, and titanium sulfate prepared from industrial-grade titanium ore; and the oxidant is one or more of hydrogen peroxide, air, oxygen, and ozone.
3. The method for preparing low-aluminum titanium-doped iron phosphate according to claim 1, characterized in that: In S1, the molar ratio of iron to phosphorus in the ferrous source and phosphorus source is 0.95~1.05; the amount of oxidant used is to reduce the amount of Fe in the ferrous source. 2+ Completely oxidized to Fe 3+ The required theoretical molar amount is 110% to 130%.
4. The method for preparing low-aluminum titanium-doped iron phosphate according to claim 1, characterized in that: In S1, the ligand is a fluorine-containing ligand; the molar ratio of the ligand to the aluminum element in the aluminum-containing titanium source is 1~100:
1.
5. The method for preparing low-aluminum titanium-doped iron phosphate according to claim 4, characterized in that: The fluorine-containing ligand is one or more of ammonium fluoride, sodium fluoride, and potassium fluoride.
6. The method for preparing low-aluminum titanium-doped iron phosphate according to claim 1, characterized in that: In S2, the precipitant includes one or more of ammonia, sodium hydroxide, and potassium hydroxide; the pH is adjusted to 1.8~2.
2.
7. The method for preparing low-aluminum titanium-doped iron phosphate according to claim 1, characterized in that: In S2, the ligand is added to at least one of the ferrous source, phosphorus source, aluminum-titanium source or oxidant before the start of the coprecipitation reaction, or is added to the reaction system in parallel with at least one of the ferrous source, phosphorus source, aluminum-titanium source and oxidant.
8. The method for preparing low-aluminum titanium-doped iron phosphate according to claim 1, characterized in that: In step S3, the filtrate from the first solid-liquid separation and the wash water after washing the first filter residue are collected. A regenerating agent is added to the combined liquid of the filtrate and wash water. After solid-liquid separation, aluminum-containing precipitate is removed to obtain regenerated mother liquor. After adding a coordinating agent to the regenerated mother liquor, the process is returned to step S2 for recycling.
9. The method for preparing low-aluminum titanium-doped iron phosphate according to claim 8, characterized in that: The regenerant includes one or more of sodium salts, calcium salts, and magnesium salts.
10. A low-aluminum titanium-doped iron phosphate prepared by the method according to any one of claims 1 to 9, characterized in that: The low-aluminum titanium-doped iron phosphate contains less than 80 ppm of aluminum, 500-10000 ppm of titanium, and has an iron-to-phosphorus molar ratio of 0.95-0.97.
Citation Information
Patent Citations
Method for separating aluminum element from waste lithium iron phosphate material
CN112310500A
A method for removing aluminum from acid leachate of spent lithium iron phosphate batteries by iron-aluminum coprecipitation
CN113816353B
Titanium-containing iron phosphate and preparation method thereof
CN121931344A
High-purity homogeneous titanium-doped iron phosphate and low-cost preparation method thereof
CN122079104A